The role of emotion regulation in chronic pain: A systematic literature review - Koechlin, Helen; Coakley, Rachael; Schechter, Neil; Werner, Christoph; Kossowsky, Joe (Journal of psychosomatic research, 2018)
Emotion regulation (ER) includes a set of cognitive and attentional processes used to change or maintain emotional state. A small but growing body of research suggests that maladaptive ER might be a risk factor for the development of chronic pain. This review aims to summarize existing literature on the association between ER and chronic pain, and to determine whether the construct of ER may further enhance our understanding of the risk and protective factors that may contribute to the onset and maintenance of chronic pain. A systematic search was conducted using the search terms “chronic pain” and “emotion regulation.” Studies that measured both constructs across all age groups were included. We found 15 studies that met our inclusion criteria. Nine studies were completed within the last five years, suggesting that the evaluation of ER as it relates to pain is a new line of research. Studies that measured “response-focused” ER found associations between maladaptive ER and pain. Studies that measured “antecedent-focused” ER strategies were less likely to show a direct association with pain. Maladaptive response-focused ER may be an important risk factor in the development and maintenance of chronic pain, as it is associated with pain and psychological comorbidities. Adding ER to chronic pain investigations may help to further explain individual differences in the risk and protective mechanisms that are known to influence chronic pain. Importantly, this line of research has potential to directly inform future interventions for patients with chronic pain. [Display omitted] •Little is known about how emotion regulation (ER) may influence pain and psychological comorbidities.•This review presents and summarizes antecedent- and response-focused ER and their association to chronic pain.•Relationship between ER and pain seemed to be mediated by psychological factors e.g. emotionality, anxiety, negative mood.•Studies on response-focused ER provided evidence for a relationship between maladaptive ER, psychological symptoms, and pain.•Adding ER to current theoretical frameworks of chronic pain may help to clarify why some people are more vulnerable than others.